Effect of rosuvastatin on the concentration of each fatty acid in the fraction of free fatty acids and total lipids in human plasma: The role of cholesterol homeostasis - Cristian I. Ciucanu (Biochemistry and Biophysics Reports, 2020)
Each fatty acid (FA) or class of FAs has a different behavior in the pathologies of atherosclerosis. The aim of this study was to investigate changes in the concentration of each fatty acid in the fraction of free fatty acids (FFAs) and total lipids in human plasma after short-term therapy with rosuvastatin as a cholesterol-lowering statin drug. Six hypercholesterolemic men on a habitual diet were studied in a randomized, double-blind, and crossover process. They received 20 mg rosuvastatin or placebo in random order, each for 4 weeks and after 2 weeks of washout period, they received another medication (placebo or rosuvastatin) for another period of 4 weeks. Rosuvastatin treatment significantly decreased the absolute concentrations of saturated and monounsaturated FAs in the total FAs as well as in FFAs. Long chain polyunsaturated fatty acids with 20 and 22 carbon atoms in the molecule had no significant change in the fraction of FFAs. Rosuvastatin is directly involved in cholesterol biosynthesis and indirectly through cholesterol homeostasis in the biosynthesis of other plasma lipids.In conclusion, our findings show that rosuvastatin treatment leads to significant changes in the concentration of each fatty acid, except for long-chain polyunsaturated fatty acids in FFAs. Our observations indicate that cholesterol homeostasis through its regulatory mechanisms appears to be the main cause of changes in the concentration of each plasma fatty acid during rosuvastatin treatment. These changes can be a source of beneficial consequences, in addition to lowering low-density lipoprotein cholesterol in cardiovascular diseases.